VD_FINDINFO Arrêt / 2020 / 436 vom 11. Mai 2020 - VD Tribunal cantonal (2020)
DÉCISION D'IRRECEVABILITÉ, PROLONGATION DU DÉLAI, MOTIVATION DE LA DEMANDE, FORME ÉCRITE | 145 CC, 450 al. 3 CC, 144 al. 1 CPC (CH)